Hypoxia treatment reverses neurodegenerative disease in a mouse model of Leigh syndrome - Ferrari, Michele (Proc Natl Acad Sci U S A, 2017)
The most common pediatric mitochondrial disease is Leigh syndrome, an episodic, subacute neurodegeneration that can lead to death within the first few years of life, for which there are no proven general therapies. Mice lacking the complex I subunit, Ndufs4, develop a fatal progressive encephalopathy resembling Leigh syndrome and die at ≈60 d of age. We previously reported that continuously breathing normobaric 11% O(2) from an early age prevents neurological disease and dramatically improves survival in these mice. Here, we report three advances. First, we report updated survival curves and organ pathology in Ndufs4 KO mice exposed to hypoxia or hyperoxia. Whereas normoxia-treated KO mice die from neurodegeneration at about 60 d, hypoxia-treated mice eventually die at about 270 d, likely from cardiac disease, and hyperoxia-treated mice die within days from acute pulmonary edema. Second, we report that more conservative hypoxia regimens, such as continuous normobaric 17% O(2) or intermittent hypoxia, are ineffective in preventing neuropathology. Finally, we show that breathing normobaric 11% O(2) in mice with late-stage encephalopathy reverses their established neurological disease, evidenced by improved behavior, circulating disease biomarkers, and survival rates. Importantly, the pathognomonic MRI brain lesions and neurohistopathologic findings are reversed after 4 wk of hypoxia. Upon return to normoxia, Ndufs4 KO mice die within days. Future work is required to determine if hypoxia can be used to prevent and reverse neurodegeneration in other animal models, and to determine if it can be provided in a safe and practical manner to allow in-hospital human therapeutic trials.